Using multiple hypothesis in model-based tracking - Teulière, Céline; Marchand, Eric; Eck, Laurent (2010 IEEE International Conference on Robotics and Automation, 2010)
Classic registration methods for model-based tracking try to align the projected edges of a 3D model with the edges of the image. However, wrong matches at low level can make these methods fail. This paper presents a new approach allowing to retrieve multiple hypothesis on the camera pose from multiple low-level hypothesis. These hypothesis are integrated into a particle filtering framework to guide the particle set toward the peaks of the distribution. Experiments on simulated and real video sequences show the improvement in robustness of the resulting tracker.